Neighborhood Effects on Tree Mortality Depend on Life Stage of Neighbors - He, Yi; Liu, Heming; Yang, Qingsong; Cao, Ye; Yin, Huimin; Zhou, Zhengkang; Yu, Qiuwu; Wang, Xihua (Frontiers in Plant Science, 2022)
Neighborhood effects are a crucial ecological process that allow species to coexist in a forest. Conspecific and heterospecific neighbors, as major classified groups, affect tree mortality through various mechanisms associating with neighbor life stages. However, how neighbor life stages influence neighborhood effects and by what mechanisms remains a knowledge gap. Here we censused the mortality of 82,202 trees representing 30 species in a 20-ha subtropical forest and classified their neighbors into the following life stages: earlier, same and later. Then, we ran generalized linear mixed models to estimate the effect of neighbors at different life stages on tree mortality. Our results showed that conspecific later stage neighbors have effects on increasing tree mortality overall, whereas conspecific earlier stage neighbors have effects on decreasing tree mortality. Furthermore, these opposing effects could offset each other so that the overall effect of conspecific neighbors on juvenile mortality seems small. In contrast, heterospecific neighbors have effects on decreasing tree mortality overall. These effects are consistent with those of later stage heterospecific neighbors. Our findings demonstrate that neighbors importantly impact tree mortality, and their specific effects are closely related to neighbor life stages. Any single effect from one neighbor life stage could disturb or dominate the total effects of the neighbors. Therefore, the neighbors must be divided into different life stages to best explain the neighborhood effect on forest dynamics.